2022
DOI: 10.3390/medicina58111512
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Kappa Free Light Chains to Diagnose Multiple Sclerosis

Abstract: Background: The positive implications of using free light chains in diagnosing multiple sclerosis have increasingly gained considerable interest in medical research and the scientific community. It is often presumed that free light chains, particularly kappa and lambda free light chains, are of practical use and are associated with a higher probability of obtaining positive results compared to oligoclonal bands. The primary purpose of the current paper was to conduct a systematic review to assess the up-to-dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 116 publications
1
3
0
5
Order By: Relevance
“…One possible explanation for these findings can be derived from considering the different structures of kappa and lambda, with the former being a monomer, while the latter tends to dimerize. Concerning MS, Arneth et al hypothesized that λ FLC dimers may have a reduced propensity to cross the blood-CSF barrier compared to monomeric k FLC [10]. If this same mechanism was confirmed in our case, it could potentially explain the observed behavior in Table 2 and Figure 3: the more severe the inflammation in the peripheral nervous system (PNS), the higher the levels of both of these markers in the CSF.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…One possible explanation for these findings can be derived from considering the different structures of kappa and lambda, with the former being a monomer, while the latter tends to dimerize. Concerning MS, Arneth et al hypothesized that λ FLC dimers may have a reduced propensity to cross the blood-CSF barrier compared to monomeric k FLC [10]. If this same mechanism was confirmed in our case, it could potentially explain the observed behavior in Table 2 and Figure 3: the more severe the inflammation in the peripheral nervous system (PNS), the higher the levels of both of these markers in the CSF.…”
Section: Discussionsupporting
confidence: 70%
“…Aside from NfL, other circulating and cerebrospinal fluid markers are starting to attract attention for a more in-depth characterization of neuroinflammatory diseases. For instance, in multiple sclerosis (MS), altered levels of free light chains (FLCs) have also been identified in both blood and CSF [10,11]. Notably, a recent meta-analysis by Arneth et al has suggested the potential benefits of utilizing FLCs for the diagnosis of MS and clinically isolated syndrome (CIS) due to the efficiency and cost-effectiveness of their isolation and analysis [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of oligoclonal bands (OCBs) in the cerebrospinal fluid (CSF) is a diagnostic marker ( 3 ) and a negative predictor of MS evolution, indicating a greater progression in OCB-positive patients ( 4 ). Moreover, a measure of intrathecal production of kappa-free light chains is gaining interest as a quantitative alternative to OCB which is also a valuable diagnostic tool ( 5 , 6 ) and predicts early activity of the disease ( 7 ). Currently, one of the most promising biomarkers is neurofilaments, which are cytoskeletal proteins released from damaged axons into the CSF and the blood.…”
Section: Introductionmentioning
confidence: 99%
“…В последние годы содержание свободных легких цепей иммуноглобулинов в ЦСЖ рассматривается как потенциальный маркер РС, а также как возможный предиктор воспалительной активности заболевания [12].…”
unclassified